A Cyclometalated IrIII Complex Conjugated to a Coumarin Derivative Is a Potent Photodynamic Agent against Prostate Differentiated and Tumorigenic Cancer Stem Cells - Novohradsky, Vojtech; Markova, Lenka; Kostrhunova, Hana; Kasparkova, Jana; Ruiz, José; Marchán, Vicente; Brabec, Viktor (Chemistry (Weinheim an der Bergstrasse, Germany), 2021)
A cyclometalated IrIII complex conjugated to a far-red-emitting coumarin, IrIII -COUPY (3), was recently shown as a very promising photosensitizer suitable for photodynamic therapy of cancer. Therefore, the primary goal of this work was to deepen knowledge on the mechanism of its photoactivated antitumor action so that this information could be used to propose a new class of compounds as drug candidates for curing very hardly treatable human tumors, such as androgen resistant prostatic tumors of metastatic origin. Conventional anticancer chemotherapies exhibit several disadvantages, such as limited efficiency to target cancer stem cells (CSCs), which are considered the main reason for chemotherapy resistance, relapse, and metastasis. Herein, we show, using DU145 tumor cells, taken as the model of hormone-refractory and aggressive prostate cancer cells resistant to conventional antineoplastic drugs, that the photoactivated conjugate 3 very efficiently eliminates both prostate bulk (differentiated) and prostate hardly treatable CSCs simultaneously and with a similar efficiency. Notably, the very low toxicity of IrIII -COUPY conjugate in the prostate DU145 cells in the dark and its pronounced selectivity for tumor cells compared with noncancerous cells could result in low side effects and reduced damage of healthy cells during the photoactivated therapy by this agent. Moreover, the experiments performed with the 3D spheroids formed from DU145 CSCs showed that conjugate 3 can penetrate the inner layers of tumor spheres, which might markedly increase its therapeutic effect. Also interestingly, this conjugate induces apoptotic cell death in prostate cancer DU145 cells associated with calcium signaling flux in these cells and autophagy. To the best of our knowledge, this is the first study demonstrating that a photoactivatable metal-based compound is an efficient agent capable of killing even hardly treatable CSCs.
Keywords: nádorové buněčné linie; apoptóza; coumarin photoactivation; prostate cancer; mužské pohlaví; nádory prostaty; Cell Line, Tumor; cancer stem cells; iridium; Antineoplastic Agents; Coumarins; oxidative stress; protinádorové látky; Prostatic Neoplasms; Humans; kumariny; Neoplastic Stem Cells; nádorové kmenové buňky; apoptosis; lidé; Male; Apoptosis; antitumor agents